Numerical Simulation of Flow around a Spur Dike with Free Surface Flow in Fixed Flat Bed - Kafle, Mukesh Raj (Journal of the Institute of Engineering, 2014)
This paper presents a numerical model to simulate two- dimensional flow near a spur-dike. The Computational Fluid Dynamics (CFD) program namely Nays 2D has been used to simulate the flow field in a fixed flat bed around the spur dike introduced into the flow at 90° to the stream-wise direction. Cubic-Interpolated Pseudo-Particle (CIP) method was used as finite difference method to analyze the advection terms. In addition, several turbulence closurer models k-ε model, zero equation model and constant eddy viscosity model were applied and compared in order to achieve the best result. The simulated results were compared with existing experimental and computed data which agreed satisfactorily. Achieved results can prove that flow structure simulation around a spur dike could be done by Nays 2D numerical modelling very well. This paper presents a numerical model to simulate two- dimensional flow near a spur-dike. The Computational Fluid Dynamics (CFD) program namely Nays 2D has been used to simulate the flow field in a fixed flat bed around the spur dike introduced into the flow at 90° to the stream-wise direction. Cubic-Interpolated Pseudo-Particle (CIP) method was used as finite difference method to analyze the advection terms. In addition, several turbulence closurer models k-ε model, zero equation model and constant eddy viscosity model were applied and compared in order to achieve the best result. The simulated results were compared with existing experimental and computed data which agreed satisfactorily. Achieved results can prove that flow structure simulation around a spur dike could be done by Nays 2D numerical modelling very well. DOI: http://dx.doi.org/10.3126/jie.v9i1.10676 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 107–114